2011
DOI: 10.1590/s1516-35982011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Bayesian models for genotype × environment estimates in post-weaning gain of Hereford bovine via reaction norms

Abstract: -It was evaluated statistical models with different assumptions to define the one that best describes the presence of genotype × environment interaction on adjusted post-weaning weight gain (PWG345) of Hereford cattle, through the study of reactions norms to the environment, obtained by random regression using a Bayesian approach.Four reaction norms hierarchical models (RNHM) were used through the INTERGEN program. The RNHM K uses the solutions of contemporary groups previously estimated by the standard animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
4
24
0
6
Order By: Relevance
“…The a posteriori mean estimates of PWG heritability from the MAMRNH model for different AN and NE breed groups were all directly proportional to the environmental gradient (Figure 2). Similar results have been found in other studies of post-weaning gain in beef cattle (Corrêa et al, 2009;Cardoso et al, 2011;Mattar et al, 2011;Cardoso and Tempelman, 2012;Santana et al, 2013), and in dairy cattle for production and reproductive traits (Kolmodin et al, 2002;Shariati et al, 2007). These results indicate that heritability increases as environmental conditions improve.…”
Section: Fixed Genetic Effectssupporting
confidence: 88%
See 3 more Smart Citations
“…The a posteriori mean estimates of PWG heritability from the MAMRNH model for different AN and NE breed groups were all directly proportional to the environmental gradient (Figure 2). Similar results have been found in other studies of post-weaning gain in beef cattle (Corrêa et al, 2009;Cardoso et al, 2011;Mattar et al, 2011;Cardoso and Tempelman, 2012;Santana et al, 2013), and in dairy cattle for production and reproductive traits (Kolmodin et al, 2002;Shariati et al, 2007). These results indicate that heritability increases as environmental conditions improve.…”
Section: Fixed Genetic Effectssupporting
confidence: 88%
“…Despite being opposite in sign, these results were similar to those obtained by Cardoso et al (2011), where residual variance increased slightly (scaling factor = 1.007) as the environmental gradient indicated conditions that were more conducive to growth. Indications robustness and heteroscedasticity were similar to those obtained without considering G × E interaction for MAMH and by Oliveira et al (2011).…”
Section: Fixed Genetic Effectssupporting
confidence: 83%
See 2 more Smart Citations
“…In general, higher direct heritabilities were observed in extreme favorable environments (Figure 2 Several authors studying the postweaning performance of beef cattle reported changes in genetic parameters across the environmental gradient, with the observation of a higher proportion of phenotypic variation due to genetic factors in more favorable environments (Corrêa et al, 2009;Cardoso et al, 2011;Mattar et al, 2011). Heritability is a property of the population and of the environment to which the animal is exposed, whereas environmental variance depends on production and management conditions.…”
Section: Resultsmentioning
confidence: 98%